Alternative hosts of Curtobacterium flaccumfaciens pv. flaccumfaciens, causal agent of bean bacterial wilt - Gonçalves, Ricardo M.; Schipanski, Carlos A.; Koguishi, Lincom; Soman, José M. [UNESP]; Sakate, Renate K. [UNESP]; Júnior, Tadeu A. F. Silva; Maringoni, Antonio C. [UNESP] (Springer Nature, 2017)
Alternative hosts are an important way of phytopathogenic bacteria survival between crop seasons, constituting a source of inoculum for the following crops. Bacterial wilt, caused by Curtobacterium flaccumfaciens pv. flaccumfaciens (Cff), is one of the most important diseases for common bean, and little information is available about the host range of the bacterium. In this study, we assessed possible alternative hosts for Cff, especially those cultivated during winter, in rotation systems with common bean. Plants of barley, black oat, canola, radish, ryegrass, wheat and white oat, were assessed under field and greenhouse conditions. Cff colonized epiphytically all plant species and endophytically black oat, ryegrass, wheat and white oat plants assessed in the greenhouse assays. Under field conditions, Cff colonized all plant species by except radish. All bacterial strains re-isolated from the plants were pathogenic to common bean and identified as Cff by PCR with specific primers. Based on our results, the cultivation of bean crop in succession with barley, black oat, canola, ryegrass, wheat and white oat should not be recommended, mainly in areas with a history of bacterial wilt occurrence. In these cases, the better option for crop rotation during the winter is radish, a non-alternative host for Cff.
Keywords: Crop rotation; Curtobacterium flaccumfaciens pv. flaccumfaciens; Disease management; Ecology; Survival; Winter crops